2011
DOI: 10.3382/ps.2010-01240
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary fluoride on growth and bone mineralization in broiler chicks

Abstract: Fluoride has been shown to have varying degrees of beneficial effects on bone mineralization and bone strength, despite its toxic effects on growth and leg disorders. Some studies have demonstrated an increase in bone ash resulting from F supplementation. The purpose of the present study was to determine whether low levels of dietary F would have any beneficial effect on the bone strength and leg disorders of young chicks fed P-deficient diets. Effects on BW and feed efficiency were also observed to monitor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Especially, rapid growth of the body and bone during the early growth phase of a broiler is suggested as one of the main causes of poor bone quality in fast growing broilers ( Williams et al, 2000 , 2004 ; Tompkins et al, 2022a ; 2022b ). To minimize economic losses and concerns about animal welfare caused by the leg bone problems of broilers, genetic factors should also be considered and investigated in addition to other aspects including nutritional and environmental factors ( Shim et al, 2011 ; Liu et al, 2015 ; Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, rapid growth of the body and bone during the early growth phase of a broiler is suggested as one of the main causes of poor bone quality in fast growing broilers ( Williams et al, 2000 , 2004 ; Tompkins et al, 2022a ; 2022b ). To minimize economic losses and concerns about animal welfare caused by the leg bone problems of broilers, genetic factors should also be considered and investigated in addition to other aspects including nutritional and environmental factors ( Shim et al, 2011 ; Liu et al, 2015 ; Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Normal development of the bone is very important in meat-type broilers. Abnormal development of the bone (such as tibial dyschondroplasia, rickets, femoral head necrosis, and perosis) can lead to severe economic losses to the poultry industry and directly compromise poultry welfare 1 5 . Although these problems are of great concern for researchers around the world, the underlying etiology of tibial dyschondroplasia (TD) is not fully understood 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that low concentrations of fluoride are essential for the development of teeth and bones in humans and animals. However, excessive fluoride ingestion has adverse effects and causes several health problems. Existing studies have shown that fluorosis causes damage to the heart through mechanisms that include induction of oxidative damage and induction of cardiomyocyte apoptosis. , However, the mechanism of fluoride cardiotoxicity in relation to inflammatory damage remains unclear.…”
Section: Discussionmentioning
confidence: 99%